Representasi Kemiskinan dalam Novel Teruslah Bodoh Jangan Pintar Karya Tere Liye - Salsabila Talaa; Moh. Karmin Baruadi; Sitti Rachmi Masie (Sasdaya: Gadjah Mada Journal of Humanities, 2026)
This research examines the representation of poverty in the novel Teruslah Bodoh Jangan Pintar by Tere Liye. The research focuses on identifying forms of poverty using Robert Chambers' theory of poverty. The method used is a qualitative descriptive approach with content analysis, based on an in-depth reading of the novel. The research results show that the novel portrays poverty as a multidimensional issue encompassing material poverty, physical weakness, isolation, vulnerability in emergency situations, and powerlessness. These representations are revealed through the depiction of characters, social conflicts, and the impacts of environmental exploitation resulting from mining activities that oppress local communities.This research affirms the novel's important role as a medium of social expression that goes beyond mere entertainment. The novel is positioned as a narrative that reflects social dynamics while also serving as a medium for critiquing the structural inequality and injustice experienced by marginalized communities. By examining the representation of poverty in literary works, this study enriches discourse by presenting critical perspectives on the relationship between literary texts and the social realities that underlie them. The findings of this research have practical relevance for developing literature-based teaching materials that are sensitive to social issues and can serve as an educational medium for readers to understand the complex dimensions of poverty portrayed in contemporary Indonesian literary works.